Sierra Leone : Selected Issues. (IMF Staff Country Reports; Country Report, 2020)
This Selected Issues paper on Sierra Leone shows that boosting education and its quality for all children yields substantial macroeconomic gains. While investments in the sector will take time to yield results, the potential gains provide ample motivation for sustained, multi-pronged policy interventions along the lines highlighted in the following paragraphs. Equalizing access to education emerges as a critical goal for prosperity that is shared fairly across the population. Attaining free secondary education for all is a critical long-run objective. With limited fiscal space and vast challenges in the sector, evidence-based prioritizing, sequencing and targeting of policies is critical. Careful monitoring of education spending and its impacts will help reassess programs and priorities going forward. Enhancing the governance of the sector to ensure that spending is well-aligned with needs in the various levels is also important. Tackling the education challenge will require coordinated work to overcome hurdles in several sectors. Several factors currently within and beyond the education sector constrain efforts that could effectively reap the economic benefits from education. The results indicate the macroeconomic benefits of education could be substantial, in the order of up to 40 percent of gross domestic product in the long run.